2017
DOI: 10.4236/jst.2017.72002
|View full text |Cite
|
Sign up to set email alerts
|

Study of an Omnidirectional Guide Wave Sensor Using an EMAT

Abstract: Nondestructive inspection of structures is important for ensuring the safety of the social infrastructure. Among them, the ultrasonic inspection method plays a role as a major technology. However, when examining a huge structure, the inspection time tends to be very long. Therefore, a system for transmitting and receiving ultrasonic waves in all directions from the ultrasonic sensor has been constructed. Several types of ultrasonic sensors using this concept have already been devised, but since the ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several different research groups have investigated multiple omnidirectional sensor system designs. The majority of them have reported that the probes are based on a sparse array of omnidirectional piezoelectric or electromagnetic acoustic transducer (EMAT) probes utilizing a shear horizontal or Lamb wave modes of guided waves [1][2][3][4][5][6][7]. Every sensor in these arrays is designed to send and receive guided waves in all directions.…”
Section: Introductionmentioning
confidence: 99%
“…Several different research groups have investigated multiple omnidirectional sensor system designs. The majority of them have reported that the probes are based on a sparse array of omnidirectional piezoelectric or electromagnetic acoustic transducer (EMAT) probes utilizing a shear horizontal or Lamb wave modes of guided waves [1][2][3][4][5][6][7]. Every sensor in these arrays is designed to send and receive guided waves in all directions.…”
Section: Introductionmentioning
confidence: 99%